2021
DOI: 10.3390/socsci10080305
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating Multiple Identities of Brazilian Paralympians

Abstract: In this article, I draw on the personal narratives of 41 Brazilian Paralympic athletes who competed in the 2016 Rio Paralympic Games to explore their multiple identities shaped within and outside sport and how they negotiated those self-representations. Parathletes’ narratives gave a sense of who they are, how they live their lives, and what their struggles, hopes, and aspirations are within and outside sport. The available studies in disability sport and the representation of disabled athletes have largely fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Certainly, such Paralympic coverage by the host broadcaster, which broadcast live for over 12 h per day on free-to-air TV and another 12 h streaming per day on 16 channels, would have been noticed. The largely consistent use of person-first language across both televised and print media is perhaps unsurprising, as this sits front and centre of the guidelines for reporting on para-athletes (IPC, 2021). This person-first spotlight was intensified by the IPC when it released WeThe15 campaign, which was pitched as the sport's greatest human rights movement aimed at ending discrimination against people with disabilities by raising visibility and participation in an effort to create a more inclusive society (Siegfried et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, such Paralympic coverage by the host broadcaster, which broadcast live for over 12 h per day on free-to-air TV and another 12 h streaming per day on 16 channels, would have been noticed. The largely consistent use of person-first language across both televised and print media is perhaps unsurprising, as this sits front and centre of the guidelines for reporting on para-athletes (IPC, 2021). This person-first spotlight was intensified by the IPC when it released WeThe15 campaign, which was pitched as the sport's greatest human rights movement aimed at ending discrimination against people with disabilities by raising visibility and participation in an effort to create a more inclusive society (Siegfried et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…(entire article) Kirakosyan (2021) interviewed Paralympic athletes to determine how the athletes themselves felt about media reports of the overcoming-adversity narrative and found that while they agreed that coverage has progressed towards becoming more performance-oriented, there was still a long way to go in moving away from the established discourse. Despite this finding, journalists remain steadfast in their desire to promote the story of overcoming hardship and adversity for audiences.…”
Section: Focus On Overcoming Tragedy Of Acquired or Late-onset Disabi...mentioning
confidence: 99%
“…Martin et al, 2020), and tackling inherent obstacles of living with disability (Powell & Myers, 2017). Para-athletes are required to negotiate and overcome physical access, communication and financial barriers (Kirakosyan, 2021), as well as a lack of professional coaching and discriminatory societal attitudes (Alexander et al, 2020; Macdougall, O’Halloran, Shields, et al, 2017; Macdougall et al, 2015, 2016). Given these additional nuances, there is a need to fully understand para-athlete well-being experiences to assess the appropriateness of existing theoretical models of well-being for this population and in the development of relevant and effective intervention strategies and well-being support provision.…”
mentioning
confidence: 99%